Green, pervasive, and cloud computing : 11th International Conference, GPC 2016, Xi'an, China, May 6-8, 2016. Proceedings /: 11th International Conference, GPC 2016, Xi'an, China, May 6-8, 2016. Proceedings. (2016) - Unknown
No abstract available